Tathwir al Kalimat al Mutaqaṭiah fi Talim Mufradat al Lughah al Arabiyyah li Talibat a Saff al Tsamin fi al Madrasah al Tsanawiyyah al Ahliyyah al Syamilah Datuk Sulaiman Palopo - Naidin Syamsuddin; Mustafa; Rika Muti Dewi (Institut Agama Islam Negeri (IAIN) Palopo, 2022)
The objectives of the research are (1) Knowledge of the design of crossword development in teaching Arabic vocabulary to eighth grade students at the comprehensive private secondary school Datuk Suleiman Valofu. (2) Knowing the level of validity of crosswords in teaching Arabic vocabulary to eighth grade students at the National Comprehensive Secondary School Datuk Suleiman Valofu. (3) Knowing the level of crossword operation in teaching Arabic vocabulary to eighth grade students at Datuk Suleiman Valofu Comprehensive Secondary School. This research uses the Research and Development method. The participants in this research were eighth grade students at the Datuk Suleiman Valofu Comprehensive High School with 10 (10) students as the research sample. Data collection techniques use observation, questionnaire and documentation. The following Search results (1) Crossword development design in teaching Arabic vocabulary to development model D4 modified to D3; Define, Design), Development. (2) The level of crossword validity in teaching Arabic vocabulary obtained the overall calendar 3.5 in the valid category with a value of 3.5 ≥ V ≥ 2.5. (3) The level of crossword operation in teaching Arabic vocabulary obtained from the teacher's response questionnaires was 4.3 and the students' response questionnaires were 4.4 in the high category.